Cocoa certification in West Africa: The need for change - (:unkn) unknown (My University, 2019)
The goal of this chapter is to discuss various implementation challenges of current cocoa certification schemes at the farm level in West Africa. To this end, the chapter presents a selection of certification criteria (requirements) from the two leading certification schemes: UTZ Certified and Rainforest Alliance. The criteria selected exemplify typical implementation problems in the West African cocoa sector, though they are by no means an exhaustive list.
Keywords: African Research